LOGISTICS SECTOR IN TURKEY AND LOGISTICS VILLAGES - (:unkn) unknown (PRESSACADEMIA, 2016)
Globalization in every sense we live in today's condition when logistics is a basic process for all existing organization, it is on important performance values. The country's existing logistics sector is constantly growing. This growth is positively related to the economy of the country. While Turkey is the seventeenth largest economy, our foreign trade is increased. In paralel to this our logistics markets's potential has been one hundred and twenty billion dollars. With this work, it is aimed to show the improvement of Turkey's logistics and to examine of contributions if which are made by the logistics village to this sector. By making swot analysis of the logistics sector's and logistics villages' in Turkey it is aimed to represent the positive effects of the current situation on economy. Results show that the promotion of logistics villages will contribute to both the growth of logistics sector and the economy.
Keywords: Logistics sector in Turkey; logistics villages in Turkey; logistics villages in the world; logistics sector; logistics villages